Contemporary Management of 1–4 Brain Metastases - Sittenfeld, Sarah M. C.; Suh, John H.; Murphy, Erin S.; Yu, Jennifer S.; Chao, Samuel T. (Frontiers in Oncology, 2018)
Brain metastases remain the most common neurologic complication of cancer. With improvement in surveillance and systemic therapy, patients with limited CNS disease are living longer after diagnosis, thus influencing the importance of optimal radiation treatment in order to maximize local control and minimize morbidity. In patients with a limited number of brain metastases, stereotactic radiosurgery is more recently seen as an appropriate sole modality for management with excellent local control. As newer systemic therapies emerge and with the advent of immunotherapies and targeted therapies for metastatic CNS disease, further research is needed in the optimal timing and sequencing of these modalities.